Students Experience of Coping with Public Speaking Anxiety: A Qualitative Study on Overthinking and Self-Confidence - Husniyah Faiha Jauharah; Fitriah M. Suud (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
Public speaking anxiety is a significant psychological barrier for students, but the role of overthinking and its relationship with self-confidence has never been studied in an integrated manner. This study aims to explore in depth students' subjective experiences related to public speaking anxiety triggered by overthinking and its impact on self-confidence. Using a qualitative method with a transcendental phenomenological design, data were collected through semi-structured in-depth interviews and analysis using epoche, horizonalitation, theme reduction, and textural, structural, and essential descriptions. The results of the study showed that anxiety manifested multi-layered in the physiological, cognitive, and behavioral dimensions triggered by Fear of Negative Evaluation (FNE). Overthinking operates as repetitive negative thinking (RNT) in the anticipatory, active (mind blank), and ruminative phases after performance. It was also found that a reciprocal relationship (vicious cycle) where low self-confidence triggers overthinking, which then gradually erodes students' self-confidence. Despite Islamic spirituality, this mechanism has not been well structured. This research implies the importance of a holistic psychoeducational intervention program that integrates cognitive reconstruction and spiritual values.